Pan-genome of Citrullus genus highlights the extent of presence/absence variation during domestication and selection - Yang Sun; Dou-Rong Kou; Yan Li; Jiang-Ping Ni; Jing Wang; Yong-Mei Zhang; Qing-Nan Wang; Bin Jiang; Xu Wang; Yue-Xin Sun; Xin-Tong Xu; Xiao-Juan Tan; et al. (BMC Genomics, 2023)
Abstract The rich genetic diversity in Citrullus lanatus and the other six species in the Citrullus genus provides important sources in watermelon breeding. Here, we present the Citrullus genus pan-genome based on the 400 Citrullus genus resequencing data, showing that 477 Mb contigs and 6249 protein-coding genes were absent in the Citrullus lanatus reference genome. In the Citrullus genus pan-genome, there are a total of 8795 (30.5%) genes that exhibit presence/absence variations (PAVs). Presence/absence variation (PAV) analysis showed that a lot of gene PAV were selected during the domestication and improvement, such as 53 favorable genes and 40 unfavorable genes were identified during the C. mucosospermus to C. lanatus landrace domestication. We also identified 661 resistance gene analogs (RGAs) in the Citrullus genus pan-genome, which contains 90 RGAs (89 variable and 1 core gene) located on the pangenome additional contigs. By gene PAV-based GWAS, 8 gene presence/absence variations were found associated with flesh color. Finally, based on the results of gene PAV selection analysis between watermelon populations with different fruit colors, we identified four non-reference candidate genes associated with carotenoid accumulation, which had a significantly higher frequency in the white flesh. These results will provide an important source for watermelon breeding.